Designing Meeting Point Syi'ah-Sunni in Indonesia - Jamaruddin, Ade; May, Asmal (The Pontianak State Institute of Islamic Studies, 2020)
Movement of thought always influences the human condition both positive and negative influences. The emergence of a belief stream begins with a movement that seeks to reconstruct, purify, innovate against conventional and normative teachings in a religion. One of the schools of Islam is Syi'ah. This research is library research, which is descriptive, analytical and comparative. The data analysis used is deductive and descriptive normative. The factor of the differences in Syi'ah's character in Indonesia is not because of the Indonesian culture. However, Syiah level of understanding of the doctrine of the Imamate gave birth to a different typology. The Indonesian cultural factors only color the skin, not to change the view of faith. The difference between the understanding of Shi'a and Sunni, according to him, the trigger of conflict and mutual infidelity is to forgive, cannot be united until the end. If the Sunni forgives Syi'ah, clearly the opposite will happen, one way that must be taken is mutual tolerance. The rationale for the Shiites is to practice it because of the reason they hold to a strong proposition. The view of the Syi'ah towards his understanding is the same as that of the Sunnah expert on his understanding.